Perancangan Antena Komunikasi Selular Generasi ke-5 pada Frekuensi 2.350 MHz di Indonesia - David Gideon; Ruliyanta Ruliyanta; Rianto Nugroho (Universitas Nasional, 2023)
The current development of the cellular communication system has ushered in the 5G telecommunications era. The government has provided a 2.3 GHz frequency spectrum for 5G implementation in Indonesia. The frequency value used in the implementation of 5G technology in Indonesia which has just started can be said to have a high impact with a high attenuation value, so an antenna with the right dimensions and parameters is needed to be used in the application of 5G technology. In this study, a microstrip antenna was designed and manufactured with a 2x8 patch circular array shape working at a frequency of 2,350 MHz for application to 5G technology using the microstrip line feed feeder method. The design and manufacture of the antenna design utilize the Ansys HFSS application and uses the FR-4 Epoxy substrate with a dielectric constant value of 4.4, a substrate thickness of 1.6 mm, and a patch made of copper. The results of the design based on the simulation results obtained the working frequency value at 2,350 MHz with a return loss value of -21.9711 dB and a wide bandwidth of 109 MHz. The VSWR value obtained is 1.0849 with a gain value of 10.06 dB and a directional radiation pattern. Based on the results of the analysis, the microstrip antenna design test has good parameter values from previous studies at the same working frequency and the microstrip antenna is suitable for use to support the development of 5G technology.